The evolution of creaky voice use in read speech by native-French and native-English speakers in tandem: a pilot study - Claire Pillot-Loiseau; Céline Horgues; Sylwia Scheuer; Takeki Kamiyama (Anglophonia)
Creaky voice is a non-modal (non-neutral) speech feature occurring both at the segmental and suprasegmental levels of languages. It also performs paralinguistic, stylistic, sociolinguistic and extra-linguistic functions. It has been reported as prevalent in (especially American) English but it is rarely described in French.During tandem exchanges between native-French speakers and native-English speakers, does voice quality found in each of the 2 languages spoken evolve in the course of the interactions? In this pilot study of read speech by 9 French/English tandem pairs (undergraduate Francophone and Anglophone students paired up), how do the number and duration of creaky occurrences vary according to: the language spoken (French or English), the language status (L1 or L2), the speaker, and the segmental or suprasegmental contexts?Creaky occurrences were manually annotated. Their frequency and duration were calculated for the 9 native French female speakers and the 9 native English speakers (eight women, one man).They were found to be more frequent among the Anglophones (in both languages) than their Francophone counterparts (transfer of creaky voice production from English to French for Anglophones), and more frequent when the Francophones spoke in English rather than French (after 3 months of interaction), with a high degree of inter-speaker variability. Moreover, the relative durations of creaky occurrences were similar in both languages spoken by the Francophones, while for the Anglophones, they were shorter in French than in English. The scope of creaky voice can be a segment, the end of stress groups, or whole intonational units (with longer occurrences). In French, glottalisation may also occur at a hiatus, especially when produced by Anglophones.This pilot study is a first step in the research of how speech interaction affects voice quality. The results obtained from read speech will have to be compared to the analysis of spontaneous speech produced by these same speakers.